Kant’s Way to the Table of Categories - Fedorchenko, Yurij (Sententiae, 2014)
The article focuses on the formation of Kant’s table of categories. The author argues that the formation of the Kantian notion of category is closely connected with the Kantian distinction between reason and understanding as cognitive capacities which Kant had not clearly distinguished for a long time, and the Kantian reinterpretation of the nature of cognitive capabilities. The author shows the three stages of Kant’s way to the table of categories and substantiates the assumption that Kant came to the idea of a metaphysical deduction of the categories as early as 1775, i.e. six years before its presentation in «Critique of Pure Reason». The author argues that Kant had two alternative approaches to the justification of the completeness of the table of categories: the inference of the table of categories on the basis of the laws of logic and metaphysical deduction of the categories, whereas in the text of «Critique of Pure Reason» Kant expounded only one approach (metaphysical deduction) with which he was not quite satisfied.